Cutis 2022
DOI: 10.12788/cutis.0636
|View full text |Cite
|
Sign up to set email alerts
|

IgA Vasculitis in the Setting of Biologic Therapy for Psoriasis and Recurrent Cutaneous Methicillin-Resistant Staphylococcus aureus Colonization

Abstract: IgA vasculitis is a form of cutaneous small-vessel leukocytoclastic vasculitis (LCV) that has various triggers, including anti-tumor necrosis factor (TNF) α therapy. As the use of more targeted biologic therapies such as the IL-17 inhibitor secukinumab increases, so do reports of associated adverse events. Herein, we describe an uncommon case of IgA vasculitis in a man undergoing biologic therapy with adalimumab and secukinumab for psoriasis with recurrent cutaneous methicillin-resistant Staphylococcus aureus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Regarding treatment, the effectiveness of corticosteroids in the prevention of severe complications and recurrence is controversial as they may mask the complications of abdominal surgery, such as fever and abdominal pain. [21][22][23] Moreover, the use of glucocorticoids may impair the healing of the incision; therefore, it is necessary to decide between creating a fistula or an anastomosis to avoid postoperative complications. We found that 24 early application of glucocorticoids in the treatment of HSP with gastrointestinal involvement is beneficial to the prevention of intussusception.…”
Section: Treatmentmentioning
confidence: 99%
“…Regarding treatment, the effectiveness of corticosteroids in the prevention of severe complications and recurrence is controversial as they may mask the complications of abdominal surgery, such as fever and abdominal pain. [21][22][23] Moreover, the use of glucocorticoids may impair the healing of the incision; therefore, it is necessary to decide between creating a fistula or an anastomosis to avoid postoperative complications. We found that 24 early application of glucocorticoids in the treatment of HSP with gastrointestinal involvement is beneficial to the prevention of intussusception.…”
Section: Treatmentmentioning
confidence: 99%